Improvement of quality control methods for linseed oils - A. I. Blyagoz (Новые технологии)
The article describes the characteristics of the developed method for determining the mass fraction of linolenic acid in linseed oil based on the method of nuclear magnetic relaxation. The quality of linseed oils is determined by the content of linolenic acid. The use of a perfect and economical method for determining the mass fraction of linolenic acid allows to determine the quality of linseed oils quickly. The purpose of the research is to substantiate the reasonability of applying the method of determining the mass fraction of linolenic acid in linseed oil based on the method of nuclear magnetic relaxation to control the quality of linseed oils. The objects of study are various samples of linseed oils that differ in fatty acid composition of triacylglycerols. Nutritional and physiological properties of linseed oil conditioned by the high content of polyunsaturated fatty acids have been characterized. A comparative characteristic of the method of gas-liquid chromatography and the method of nuclear magnetic relaxation has been given. The advantages of using the method of nuclear magnetic relaxation in comparison with the method of gas-liquid chromatography for determining the mass fraction of linolenic acid in order to establish the compliance of linseed oils with high-linolene ones have been shown. The reasonability of applying the method of determining the mass fraction of linolenic acid in linseed oil based on the method of nuclear magnetic relaxation to control the quality of linseed oils has been substantiated.